Acute infectious hepatitis in hospitalised children: a British Paediatric Surveillance Unit study. Issue 7 (4th April 2017) - Braccio, Serena; Irwin, Adam; Riordan, Andrew; Shingadia, Delane; Kelly, Deirdre A; Bansal, Sanjay; Ramsay, Mary; Ladhani, Shamez N
Abstract : Background: Hepatitis remains a key public health priority globally. Most childhood cases are caused by viruses, especially hepatitis A virus (HAV) and hepatitis B virus (HBV). This study aimed to estimate the burden of acute infectious hepatitis in hospitalised children and to describe their clinical characteristics and outcomes. Methods: Paediatricians in the UK and Ireland reported cases in children aged 1 month to 14 years diagnosed between January 2014 and January 2015 (inclusive) through the British Paediatric Surveillance Unit (BPSU) and completed a detailed questionnaire. Additional HAV and HBV cases in England and Wales were identified through a national electronic database, LabBase2. All confirmed cases were followed up at 6 months with a second questionnaire. Results: The BPSU survey identified 69 children (annual incidence, 0.52/100 000), including 27 HAV (39%), three HBV (4%), 16 other viruses (23%) and 23 with no aetiology identified (33%). LabBase2 identified an additional 10 HAV and 2 HBV cases in England. Of the 37 hospitalised HAV cases, 70% had travelled abroad, but only 8% had been vaccinated. Similarly, three of the five children with acute HBV had not been immunised, despite being a household contact of a known infectious individual. All patients with HAV recovered uneventfully. In contrast, three children with acute HBV developed liver failure and two required liver transplantation. Conclusions: Acute infectious hepatitis is a rare cause of hospital admission. Most children recovered without complications, but those with acute HBV had severe presentations. At least three of the five HBV cases could have been prevented through appopriate vaccination of household contacts.